Developmental disorders of the midbrain and hindbrain - Barkovich, Anthony J. (Frontiers in Neuroanatomy, 2012)
Malformations of the midbrain and hindbrain have become topics of considerable interest in the neurology and neuroscience literature in recent years. The combined advances of imaging, and molecular biology have improved analyses of structures in these areas of the central nervous system, while advances in genetics have made it clear that malformations of these structures are often associated with dysfunction or malformation of other organ systems. This review focuses upon the importance of communication between clinical researchers and basic scientists in the advancement of knowledge of this group of disorders. Disorders of anteroposterior patterning, cerebellar hypoplasias, disorders associated with defects of the pial limiting membrane (cobblestone cortex), disorders of the Reelin pathway, and disorders of the primary cilium/basal body organelle (molar tooth malformations) are the main focus of the review.